Characterization of a new semi-dominant dwarf allele of SLR1 and its potential application in hybrid rice breeding. (28th June 2018) - Wu, Zhigang; Tang, Ding; Liu, Kai; Miao, Chunbo; Zhuo, Xiaoxuan; Li, Yafei; Tan, Xuelin; Sun, Mingfa; Luo, Qiong; Cheng, Zhukuan
Abstract : Dwarf germplasms are very important for genetic breeding. Here, we characterize a new semi-dominant dwarf allele of SLR1 and show its potential application in hybrid rice breeding. Abstract: The widespread introduction of semi-dwarf1 ( sd1 ), also known as the 'Green Revolution' gene, has dramatically increased rice yield. However, the extensive use of limited sources of dwarf genes may cause 'bottleneck' effects in breeding new rice varieties. Alternative dwarf germplasms are quite urgent for rice breeding. Here, we characterized a new allele of the rice Slr1-d mutant, Slr1-d6, which reduced plant height by 37%, a much milder allele for dwarfism. Slr-d6 was still responsive to gibberellin (GA) to a reduced extent. The mutation site in Slr1-d6 was less conserved in the TVHYNP domain, leading to the specific semi-dominant dwarf phenotype. Expression of SLR1 and five key GA biosynthetic genes was disturbed in Slr1-d6, and the interaction between Slr1-d6 and GID1 was decreased. In the genetic background of cultivar 9311 with sd1 eliminated, Slr1-d6 homozygous plants were 70 cm tall. Moreover, Slr1-d6 heterozygous plants were equivalent in height to the standard sd1 semi-dwarf 9311, but with a 25% yield increase, showing its potential application in hybrid rice breeding.